Funding kidney research as a public health priority: challenges and opportunities. Issue 1 (4th September 2020) - Zoccali, Carmine; Vanholder, Raymond; Wagner, Carsten A; Anders, Hans-Joachim; Blankestijn, Peter J; Bruchfeld, Annette; Capasso, Giovambattista; Cozzolino, Mario; Dekker, Friedo W; Fliser, Danilo; Fouque, Denis; Gansevoort, Ron T; et al.
Abstract: Medical societies have a social responsibility to disseminate knowledge and inform health authorities on threats to public health posed by various diseases. Advocacy for health protection programmes and for medical research funding is now embedded into the missions of most scientific societies. To promote kidney research funding in Europe, the European Renal Association – European Dialysis and Transplant Association (ERA-EDTA), rather than acting as an individual society advocating for the fight against kidney disease, has actively helped to create an alliance of national associations centred on kidney diseases, the European Kidney Health Alliance (EKHA), and joined the Biomedical Alliance (BMA). The ERA-EDTA is fully committed to supporting its working groups (WGs) and consortia of its members to allow them to produce valuable kidney research. The framing and formalization of projects, and the regulatory issues related to submission to the European Commission, are complex. To help WGs to gain expert advice from agencies with specific know-how, the ERA-EDTA has adopted a competitive approach. The best research projects proposed by WGs and consortia of other European investigators will receive seed funding to cover the costs of consultancy by expert agencies. Via its broader platforms, the EKHA and the BMA, the ERA-EDTA will strive towards broader recognition of kidney disease and related clusters of non-communicable diseases, by European and national agencies, as major threats to the qualities of life of their populations and their economies.